Epidemiology of early childhood weight change and concurrent undernutrition among African children: A sub-continental observational analysis - Abiodun Adanikin; Elizabeth Eberechi Oyenusi; Adeniyi Fagbamigbe; Iretiola Fajolu (PLoS ONE, 2025)
Background Evidence on weight change among children under five in sub-Saharan Africa is limited, as is knowledge of its association with undernutrition status. This study assessed how early childhood weight change—categorised as acceleration, deceleration, or stable—following different birthweights (low, normal, or high) influences the risk of undernutrition in sub-Saharan African children. Methods Using data from 111,623 children across 33 sub-Saharan countries from recent Demographic and Health Surveys (2011–2022), weight trajectory was measured by SD score comparison for current age and birthweight. Survey-weighted logistic regression was used to estimate the odds of distinct weight changes, and of stunting, underweight, and wasting. We adjusted for individual child factors (e.g., age, sex, birth order), maternal factors (e.g., age, education, employment), household factors (e.g., family size, household wealth), and contextual factors (e.g., place of residence). Results Among the 111,623 under-five children, 24.63% had accelerated weight change, 40.84% had decelerated weight change, 26.05% were stunted, 11.80% were underweight, and 5.54% were wasted. Of the 38,343 children with ‘stable’ weight progression, 20.14% were stunted, 5.49% were underweight, and 3.27% wasted. The odds of accelerated weight gain were approximately seventeen times higher among low birthweight infants (aOR = 16.92; 95% CI: 15.78 to 18.83), while the odds of decelerated weight change were about nineteen times higher among high birthweight infants (aOR = 18.53; 95% CI: 16.44 to 20.88), compared with those of normal birthweight. Children with normal birthweight who experienced decelerated weight change had highest odds of being underweight (aOR: 14.05; 95% CI: 12.72 to 15.52), followed by LBW infants with accelerated weight gain (aOR: 4.01; 95% CI: 3.48 to 4.62), and high birthweight infants with weight deceleration (aOR: 3.61; 95% CI: 3.11 to 4.17). Conclusions Early childhood growth disruptions, especially weight deceleration, are common in sub-Saharan African children. The complex relationship between birthweight, subsequent weight progression, and undernutrition underscores the need to address poverty to prevent growth disruptions and ensure comprehensive growth assessments during healthcare contact by infants to identify suboptimal growth and provide necessary support to address it.